Financial leverage and corporate taxation: evidence from German corporate tax return data - Nadja Dwenger; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We estimate the impact of effective profit taxation on the financial leverage of corporations on the basis of a pseudo-panel constructed from corporate tax return micro data for the period 1998-2001, a period which saw the introduction of a major corporate tax reform in Germany. The financial leverage is measured by the ratio of long-term debt to total capital. Endogeneity of the effective corporate tax rate is controlled for by an instrumental variable approach. Our instrument for the observed effective tax rate is the counterfactual tax rate a corporation would face in a particular period had there be no endogenous change of its financial structure. This counterfactual is obtained from a detailed microsimulation model of the corporate sector based on tax return micro data. We find a statistically significant and relatively large positive effect of the tax rate on corporate leverage: on average, an increase of the tax rate by 10 percent would increase the financial leverage by about 5 percent. We also find that the debt ratio is less responsive for small corporations and for corporations that benefit from various other forms of tax shields, in particular depreciation allowances and tax loss carry-forward. However, tax effects do not seem to depend on risk, although the level of economic risk does affect corporate leverage.
Keywords: G32; G38; H25; H32; 330; Financial leverage; financial structure; debt ratio; corporate income taxation; corporate tax return data; Körperschaftsteuer; Unternehmensbesteuerung; Steuerbelastung; Steuerreform; Steuerwirkung; Kapitalstruktur; Deutschland